'War-fighting and left-wing feminist agendas': gender and change in the Australian Defence Force. Issue 3 (2nd September 2018) - Wadham, Ben; Bridges, Donna; Mundkur, Anuradha; Connor, James
ABSTRACT: Western military institutions are reforming to enhance gender inclusion. This imperative is driven by the need to sustain a volunteer force in a society with rapidly changing values coupled with a recognition that sustainability and legitimacy requires diverse representation from the community from which they draw their human resources. Our recent research has considered the changing character of the Australian Defence Force (ADF)'s disposition towards women, and discourse of gender and gender reform. In this paper we critically evaluate these discourses on gender equality across the ADF and outline the salient ideas and claims within institutional reviews and in academic papers written by ADF soldier–scholars. Our purpose is to interrogate current ways of framing and articulating key ideas on gender, sexuality, and equality to scrutinize the implications for the ADF's stated purpose of creating a gender-inclusive workplace. We find that the driving functional imperative of military effectiveness limits and shapes the extent to which the ADF can become a genuinely gender-inclusive workplace.